Subcutaneous Panniculitis-like T-Cell Lymphoma Without Erythema and Subcutaneous Tumors - Wakumoto, Keiko (Yonago Acta Med, 2020)
We report a case of subcutaneous panniculitis-like T-cell lymphoma with diffuse indurated lesions without erythema. A 27-year-old man was referred to us with a 1-month history of fever, general fatigue and indurated skin lesions. The initial examination revealed indurated skin lesions without erythema and subcutaneous tumors in the right lower abdomen, back and buttocks. Histopathology showed a panniculitis predominantly in lobular pattern, and infiltration of atypical lymphocytes in the subcutaneous tissue. Characteristically, there was rimming of individual fat cells by surrounding atypical lymphocytes. Results of laboratory examinations showed hemophagocytic syndrome (HPS). Based on these findings, we made a diagnosis of subcutaneous panniculitis-like T-cell lymphoma without erythema and subcutaneous tumors with HPS. To our knowledge, there has been no report of SPTCL with diffuse indurated lesions without erythema, tumors, or plaque, all of which are considered to be typical characteristics of SPTCL. Positron emission tomography / computed tomography (PET/CT) showed noticeable thickening of diffuse subcutaneous involvement throughout the body. Hence, PET/CT is a useful for the detection of SPTCL as well as its distribution.